2016
DOI: 10.1182/asheducation-2016.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune and other acquired neutropenias

Abstract: This educational review addresses the diagnostic evaluation of patients for autoimmune and other forms of acquired neutropenia, including the futility of deconstructing the overlap of chronic “autoimmune,” “benign,” and “idiopathic” categories. Isolated neutropenias due to infection, drugs, and immunological disorders are also addressed. Discussion of management options emphasizes a conservative approach with largely supportive care for these mostly benign and self-limited disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 33 publications
(42 reference statements)
0
49
0
8
Order By: Relevance
“…BEN was considered as an alternative diagnosis as these patients demonstrated persistent neutropenia and their records did not indicate the presence of any infection or malignancy, thereby fulfilling the criteria for the diagnosis [ 19 ]. BEN is a clinical diagnosis [ 20 , 21 ]. However, one study found a significant association between persistent neutropenia in patients of African ancestry and polymorphism in the Duffy antigen receptor for chemokines (SNP rs2814778 at chromosome 1q23.2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BEN was considered as an alternative diagnosis as these patients demonstrated persistent neutropenia and their records did not indicate the presence of any infection or malignancy, thereby fulfilling the criteria for the diagnosis [ 19 ]. BEN is a clinical diagnosis [ 20 , 21 ]. However, one study found a significant association between persistent neutropenia in patients of African ancestry and polymorphism in the Duffy antigen receptor for chemokines (SNP rs2814778 at chromosome 1q23.2).…”
Section: Discussionmentioning
confidence: 99%
“…Benign ethnic neutropenia (BEN) is a relatively common condition throughout the Middle East, especially among those of African descent [ 19 ]. It is a clinical diagnosis based on persistent neutropenia with normal levels of other white blood cell lines, as well as the absence of secondary causes of neutropenia or hematological disorders [ 20 23 ]. There are many reports of the prevalence of BEN in Arab populations.…”
Section: Introductionmentioning
confidence: 99%
“…1 Neutropenia in AIN is a result of peripheral destruction of neutrophils due to autoantibody production against antigens on the neutrophil surface, most commonly human neutrophil antigen 1 (HNA-1) on the neutrophil immunoglobulin receptor Fc RIIIb. 8,9 Antibodies often remit within 18 to 24 months from the time of diagnosis, resulting in spontaneous remission. As a consequence, patients with AIN have lower rates of infection due to normal marrow storage pool of neutrophils and rarely develop severe infections.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils are an important part of the body’s defense system and prevent bacterial and fungal infections by phagocytosis and killing foreign invaders. A neutrophil count below 1,500 cells/μL is termed neutropenia, and it becomes clinically significant if the counts fall below 200, especially in immunocompromised states [1]. Hence, neutropenia is alarming to the patient families, as well as certain clinicians, even if it is transient.…”
Section: Introductionmentioning
confidence: 99%